EVALUASI PROGRAM PEMBINAAN OLAHRAGA PENCAK SILAT PADA IKATAN PENCAK SILAT INDONESIA (IPSI) KABUPATEN MUARA ENIM PROVINSI SUMATERA SELATAN - Hardi, Al Azis (Jurnal Dosen Universitas PGRI Palembang)
Abstract. This study was to evaluate the development of martial arts sport in Muara Enim IPSI. This study used qualitative methods, the model of stake countinance evaluation approach that uses three stages; namely antecedent, transaction, outcomes. Research conducted at Ikatan Pencak Silat Indonesia (IPSI) Muara Enim. Data sources are administrators, coaches, athletes, parents of athletes. The instruments used are observation, interviews, documentation. Results, antecedent where the background and purpose of coaching at IPSI is to preserve the original martial culture of Indonesia and embrace all existing perguruan pencak silat in Muara Enim, a place for fighters to float talent and potential for achievement, facilities and infrastructure better, support The government is, adequate human resources, no funding sources coaching, coach Transaction appointed directly, there is no specific recruitment system in determining the coach. Athletes are selected through the game every year, the implementation of the training program is not running properly, Outcomes achievement IPSI Muara Enim athlete has not reached the set target. Conclusion martial arts sports coaching at IPSI has not been good. still needed improvement. In recruiting coach let administrators owned the licenses coaching, recruiting athletes pay attention to the physical condition and health. immediately coordinate with the government in order to realize the foster parent coaching system as solving the problem of fundingKeyword : Evaluatian, Program, Pencak Silat